AN INVESTIGATION OF LISTENING COMPREHENSION STRATEGIES USED BY SIXTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT UNIVERSITY OF BENGKULU - Afrian Reastu Prayogi; Elfrida .; Mei Hardiah (Universitas Bengkulu, 2018)
This research aims to find out the listening comprehension strategies used by sixth semester students of English Education Study Program at University of Bengkulu. The subject of this research is all sixth semester students of English Education Study Program in academic year 2017/2018. This research was using descriptive quantitative as the methodology and the data was collected by using questionnaire as the instrument. The questionnaire consisted of 35 items which represent the use of listening comprehension strategies from cognitive, metacognitive, and socio-affective strategies. This research uses Statistical Package for Social Sciences (SPSS) version 22 to analyze the data. Oxford’s (1990) rating scheme for strategy use was used to determine the category of listening comprehension strategies use. The result of data analysis shows that students use cognitive, metacognitive, and socio-affective strategies in listening comprehension. Cognitive strategy was used as the most highly use of strategies in listening comprehension with the mean score 3.54 (high), followed by socio-affective strategy with the mean score 3.43 (moderate) and metacognitive strategy with the mean score 3.4 (moderate). From the results, it is concluded that students are using strategies mostly when doing a listening task at the classroom, by using the lexical and grammatical competences also background knowledge to understand the listening materials.